Descent - Smith, Roland, 1951- (Houghton Mifflin Harcourt, 2020)
After surviving an avalanche on the isolated Hkakabo Razi mountain, Peak and his team must descend into Tibet, risking the People's Liberation Army catching Peak's famous mountaineering father and their climbing guide, Zopa, who are both wanted by the Chinese government. A high-stakes game of cat and mouse follows on the dangerous mountain sides.